Cryptococcus gattii urease as a virulence factor and the relevance of enzymatic activity in cryptococcosis pathogenesis. (2nd March 2015) - Feder, Vanessa; Kmetzsch, Lívia; Staats, Charley Christian; Vidal‐Figueiredo, Natalia; Ligabue‐Braun, Rodrigo; Carlini, Célia Regina; Vainstein, Marilene Henning
<x xml:space="preserve">Abstract</x> Ureases (EC 3.5.1.5) are Ni2+‐dependent metalloenzymes produced by plants, fungi and bacteria that hydrolyze urea to produce ammonia and CO2. The insertion of nickel atoms into the apo‐urease is better characterized in bacteria, and requires at least three accessory proteins: UreD, UreF, and UreG. Our group has demonstrated that ureases possess ureolytic activity‐independent biological properties that could contribute to the pathogenicity of urease‐producing microorganisms. The presence of urease in pathogenic bacteria strongly correlates with pathogenesis in some human diseases. Some medically important fungi also produce urease, including Cryptococcus neoformans and Cryptococcus gattii. C. gattii is an etiological agent of cryptococcosis, most often affecting immunocompetent individuals. The cryptococcal urease might play an important role in pathogenesis. It has been proposed that ammonia produced via urease action might damage the host endothelium, which would enable yeast transmigration towards the central nervous system. To analyze the role of urease as a virulence factor in C. gattii, we constructed knockout mutants for the structural urease‐coding gene URE1 and for genes that code the accessory proteins Ure4 and Ure6. All knockout mutants showed reduced multiplication within macrophages. In intranasally infected mice, the ure1Δ (lacking urease protein) and ure4Δ (enzymatically inactive apo‐urease) mutants caused reduced blood burdens and a delayed time of death, whereas the ure6Δ (enzymatically inactive apo‐urease) mutant showed time and dose dependency with regard to fungal burden. Our results suggest that C. gattii urease plays an important role in virulence, in part possibly through enzyme activity‐independent mechanism(s).